Asleep at the Wheel (Again)? Bank Audits During the Lead‐Up to the Financial Crisis - Doogar, Rajib; Rowe, Stephen P.; Sivadasan, Padmakumar (Contemporary Accounting Research, 2015)
Abstract We present the first large‐sample empirical evidence on U.S. auditors' responses to changes in entity‐level audit risk during 2006–2007, the period leading up to the financial crisis of 2008–2009. Treating fiscal year 2005 engagements as a pre‐crisis benchmark, we find that audit attention during fiscal year 2006 and 2007 bank audit engagements shifted in line with the shifting audit risks. One implication of these findings is that auditors were able to recognize and respond to financial statement impacts of the macroeconomic shocks that unfolded during the lead‐up to the crisis. Another implication is that auditors' failure to issue advance warnings of increasing auditee riskiness during the time leading up to the financial crisis more likely reflects limitations of extant accounting and auditing rules rather than a lack of auditor awareness or attention to those risks.